Grouping the Distribution of Diarrhea Based on the Public Health Centers in Binjai City Using the Clustering Method - Rika Hedy Anggraini Prastio; Akim M.H Pardede; Hermansyah Sembiring (CV. AFDIFAL MAJU BERKAH, 2022)
Diarrhea is one of the endemic diseases that occurs throughout the year and is one of the highest causes of death for everyone, especially children under five in Indonesia. The purpose of this thesis is to analyze the spread of diarrheal disease by forming a grouping of the spread of diarrheal disease and to analyze the characteristics of the spread of diarrheal disease. With the development of technology that is increasingly sophisticated and easy to use, such technological developments motivate us to know the importance of using computers in fast and practical data processing. Clustering is a data analysis method, which is often included as one of the Data Mining methods, whose purpose is to group data with the same characteristics and data with different characteristics into others.